Transcranial Direct Current Stimulation and Brain–Computer Interfaces for Improving Post-Stroke Recovery: A Systematic Review and Meta-Analysis. - Lima, Eloise de Oliveira; Silva, Letícia Maria; Melo, Ana Luísa Vilar; D'arruda, Julia Vitória Torres; Alexandre de Albuquerque, Marlon; Ramos de Souza Neto, José Maurício; Araújo de Oliveira, Eliane; Andrade, Suellen Marinho (Clinical Rehabilitation, 2024)
Objective: This study aimed to evaluate the effectiveness of transcranial direct current stimulation associated with brain–computer interface in stroke patients. Data sources: The PubMed, Central, PEDro, Web of Science, SCOPUS, PsycINFO Ovid, CINAHL EBSCO, EMBASE, and ScienceDirect databases were searched from inception to April 2023 for randomized controlled studies reporting the effects of active transcranial direct current stimulation associated with brain–computer interface to a transcranial direct current stimulation sham associated with brain–computer interface condition on the outcome measure (motor performance and functional independence). Review methods: We searched for full-text articles which had investigated the effect of transcranial direct current stimulation associated with brain–computer interface on motor performance in the upper extremities in stroke patients. The standardized mean differences derived from the change in scores between pretreatment and post-treatment were adopted as the effect size measure, with a 95% confidence interval. Possible sources of heterogeneity were analyzed by performing subgroup analyses in order to examine the moderating effects for one variable: the level of injury severity. Results: Nine studies were included in the qualitative synthesis and the meta-analysis. The findings of the conducted analyses indicated there is not enough evidence to suggest that active transcranial direct current stimulation associated with brain–computer interface is more efficient in motor performance and functional independence when compared to sham transcranial direct current stimulation associated with brain–computer interface or brain–computer interface alone. In addition, the quality of evidence was rated very low. A subgroup analysis was performed for the motor performance outcome considering the injury severity level. Conclusion: We found evidence that transcranial direct current stimulation associated with brain–computer interface was not more beneficial than sham transcranial direct current stimulation associated with brain–computer interface or brain–computer interface alone.